Uterine and fetal placental Doppler indices are associated with maternal cardiovascular function - Tay, Jasmine; Masini, Giulia; McEniery, Carmel M.; Giussani, Dino A.; Shaw, Caroline J.; Wilkinson, Ian B.; Bennett, Phillip R.; Lees, Christoph C. (American journal of obstetrics and gynecology, 2019)
The mechanism underlying fetal-placental Doppler index changes in preeclampsia and/or fetal growth restriction are unknown, although both are associated with maternal cardiovascular dysfunction. We sought to investigate whether there was a relationship between maternal cardiac output and vascular resistance and fetoplacental Doppler findings in healthy and complicated pregnancy. Women with healthy pregnancies (n=62), preeclamptic pregnancies (n=13), preeclamptic pregnancies with fetal growth restriction (n=15), or fetal growth restricted pregnancies (n=17) from 24–40 weeks gestation were included. All of them underwent measurement of cardiac output with the use of an inert gas rebreathing technique and derivation of peripheral vascular resistance. Uterine and fetal Doppler indices were recorded; the latter were z scored to account for gestation. Associations were determined by polynomial regression analyses. Mean uterine artery pulsatility index was higher in fetal growth restriction (1.37; P=.026) and preeclampsia+fetal growth restriction (1.63; P=.001) but not preeclampsia (0.92; P=1) compared with control subjects (0.8). There was a negative relationship between uterine pulsatility index and cardiac output (r2=0.101; P=.025) and umbilical pulsatility index z score and cardiac output (r2=0.078; P=.0015), and there were positive associations between uterine pulsatility index and peripheral vascular resistance (r2=0.150; P=.003) and umbilical pulsatility index z score and peripheral vascular resistance (r2= 0.145; P=.001). There was no significant relationship between cardiac output and peripheral vascular resistance with cerebral Doppler indices. Uterine artery Doppler change is abnormally elevated in fetal growth restriction with and without preeclampsia, but not in preeclampsia, which may explain the limited sensitivity of uterine artery Doppler changes for all these complications when considered in aggregate. Furthermore, impedance within fetoplacental arterial vessels is at least, in part, associated with maternal cardiovascular function. This relationship may have important implications for fetal surveillance and would inform therapeutic options in those pathologic pregnancy conditions currently, and perhaps erroneously, attributed purely to placental maldevelopment. Uterine and fetal placental Doppler indices are associated significantly with maternal cardiovascular function. The classic description of uterine and fetal Doppler changes being initiated by placental maldevelopment is a less plausible explanation for the pathogenesis of the conditions than that relating to maternal cardiovascular changes.